New experience in the process of facing the past - Gajicki Marija (Temida)
In this paper the author presents the project VIVISECT, which was developed in connection to the negative reactions in several towns in Serbia to the exhibition of war photography of American photographer Ron Haviv. NGO Vojvodjanka organized the same exhibition in different way, which included removing the titles and allowing people to write their own titles and comments. As a result of that the book and documentary film VIVISECT are developed, which have been afterwards used for developing discussion about the past within community.